Someone has led this child to believe : a memoir - Louise, Regina (Bolden, 2018)
"The long-awaited follow-up to Regina Louise's critically acclaimed debut memoir Somebody's Someone. Louise's first memoir garnered positive reviews and national media attention, including spots on NPR's All Things Considered and CBS's The Early Show. An unflinching, unforgettable true story of overcoming neglect in the US foster-care system to find success. The author is a well-known for her work as a an advocate for foster children. Readers will find inspiration in this remarkable story about determination, courage, and renewal."--